Factors Affecting Employee Productivity on Government Organizations in Tanzania: A Case of Shinyanga Regional Secretariat, Tanzania - James, Elisha; Mutasa, Felician (Technium Social Sciences Journal, 2022)
The aim of this study was to examine the factors affecting employee productivity of government employees at Shinyanga Regional Secretariat in Tanzania. Government employees were the main point of the study and adopted a survey research design, an ordered logistic regression model and STATA for data analysis was applied. Sample size was 191 respondents, primary data was collected using descriptive questionnaires and triangulation. Results from the ordered logistic regression model (odds) show that, the odds of Trainings are not significant, trainings which have been asked considered all the trainings including seminars and workshops which were found not to relate to the carrier of position one holds in the office and thus it came out insignificant. Basing on the rule for significance level from the regression analysis, the coefficient of the effect of leadership style showed that, one-unit change in the effect of leadership style results in 0.087 units increase in labor productivity, meaning that, there is a significant relation (at p value of 0.000) between the effect of leadership style in Tanzania with respect to labor productivity. Therefore, we recommend that, Leadership style that is supportive and encourages is necessary in building working teams and promotes labour productivity at Shinyanga Regional Secretariat and when employees are not involved in designing, organization and planning the training, the evaluation of the training outcomes becomes difficulty. Furthermore, Leaders are to be trained on good leadership so as to apply a leadership style that works to the subordinates and there should be frequent evaluations checking if the leaders are participatory to the subordinates.